2010
DOI: 10.1111/j.1365-2036.2010.04374.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: self‐management support interventions for irritable bowel syndrome

Abstract: Many self-management support interventions appear benefit patients with irritable bowel syndrome. However, studies were limited by methodological flaws. Furthermore, feasibility in 'real world' clinical practice is uncertain. Thus, practical self-management interventions that can be applied across various clinical settings should be developed, and then tested in well-designed clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
0
21
0
1
Order By: Relevance
“…In contrast, Ford et al 192 appears to offer more evidence to support CBT, but the studies in their analysis are exactly the same as in the Cochrane review so this outcome may have arisen from their meta-analysing a larger group of more heterogeneous studies than Zijdenbos et al 193 Ford et al 192 identifies evidence of publication bias and in a sensitivity analysis 'when the three studies conducted in the same centre were excluded from the analysis, the beneficial effect of CBT on symptoms of IBS disappeared' but still goes on to endorse CBT as 'efficacious in the treatment of IBS in the short-term'. In Dorn's 191 review, the primary outcomes of the RCTs were also heterogeneous but nearly always involved symptom scores and nearly every study reported a positive primary outcome result favouring, or tending to favour, the intervention. In view of the heterogeneity (which included heterogeneity in study size, diagnostic criteria, setting and quality, in addition to intervention and outcome measures), Dorn 191 did not attempt a meta-analysis -instead presenting results of each individual studies narratively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, Ford et al 192 appears to offer more evidence to support CBT, but the studies in their analysis are exactly the same as in the Cochrane review so this outcome may have arisen from their meta-analysing a larger group of more heterogeneous studies than Zijdenbos et al 193 Ford et al 192 identifies evidence of publication bias and in a sensitivity analysis 'when the three studies conducted in the same centre were excluded from the analysis, the beneficial effect of CBT on symptoms of IBS disappeared' but still goes on to endorse CBT as 'efficacious in the treatment of IBS in the short-term'. In Dorn's 191 review, the primary outcomes of the RCTs were also heterogeneous but nearly always involved symptom scores and nearly every study reported a positive primary outcome result favouring, or tending to favour, the intervention. In view of the heterogeneity (which included heterogeneity in study size, diagnostic criteria, setting and quality, in addition to intervention and outcome measures), Dorn 191 did not attempt a meta-analysis -instead presenting results of each individual studies narratively.…”
Section: Resultsmentioning
confidence: 99%
“…Both reviews of psychological interventions 192,193 included some monocomponent interventions not considered self-management support for the purposes of this review, but both also separately presented results for CBT or multicomponent psychological support interventions separately and it is these 11 RCTS 192 and 17 RCTS 193 that are considered here. There is huge overlap between Ford et al 192 and Zijdenbos et al, 193 with only two papers in Ford et al 192 not included in Zijdenbos et al, 193 but the more broadly self-management focused Dorn 191 has only one RCT in common with Ford et al 192 and two with Zijdenbos et al …”
Section: Dornmentioning
confidence: 99%
See 3 more Smart Citations